Transport and the Greenhouse Effect: The Role of Research in Kyoto-Related Climate Policy in The Netherlands - Anne Annema, Jan Anne; van Wee, Bert (European Journal of Transport and Infrastructure Research, 2000)
To date, 84 nations have signed the so-called Kyoto Protocol on the control of Greenhouse Gas (GHG) emissions. In the Netherlands the Kyoto agreement has resulted in quantitative national targets for 2008-2012 of -6% GHG emission reduction compared to 1990; this is a reduction of 19% compared to the emission forecasted for 2010. Two years ago the Dutch government launched a policy-making process for meeting the Kyoto target. In both the development and the evaluation of Dutch Kyoto-related policy, research has played a major role. For the transport sector no (a priori) targets were set; however, a list of measures and instruments to reduce transport GHG emissions were discussed in the Kyoto-related policymaking process. Nearly all transport instruments and measures on this list appeared to be car-related. The reason for this focus was an a priori choice of policymakers. However, costeffective options for other vehicle categories (road and non-road transport) may be available. The transport options finally chosen for the Policy document will reduce GHG emissions from transport by 3-5% compared to the forecasted 2010 emissions. Researchers estimated that tax differentiation for new cars and in-car instruments such as fuel economy meters and cruise control will be the most effective instruments. The selected transport measures were not really chosen to induce a technology push; rather, the selection was mainly policy driven to meet short-term targets. Although research played a significant role in the policy-making process, several research improvements can still be made. Important improvements identified are: a) using a better and clearer method for the calculation of the costs of the measures and b) using a broader evaluation method of measures; this will mean including more environmental, economic and social indicators.